IODP Expedition 379 Magnetic remanence (SRM-longcore) - Gohl, Karsten; Wellner, Julia S.; Klaus, Adam; Bauersachs, Thorsten; Bohaty, Steven; Courtillat, Margot; Cowan, Ellen A.; De Lira Mota, Marcelo A.; Esteves, Mariana S.R.; Fegyveresi, John M.; Frederichs, Thomas; Gao, Liang; et al. (International Ocean Discovery Program, 2021)
Magnetic remanence was measured on section halves (and rarely on whole-round sections) using a 2G Enterprises 760R cryogenic magnetometer, first as natural remanent magnetization (NRM) and then after demagnetization steps were performed on the samples by alternating field (AF) demagnetizer coils mounted in-line within the instrument.